The courage to act : a memoir of a crisis and its aftermath - Bernanke, Ben S. (2017)
In 2006, Ben S. Bernanke was appointed chair of the Federal Reserve, capping a meteoric trajectory from a rural South Carolina childhood to professorships at Stanford and Princeton, to public service in Washington's halls of power. There would be no time to celebrate, however -- the burst of the housing bubble in 2007 set off a domino effect that would bring the global financial system to the brink of meltdown. Here, Ben Bernanke pulls back the curtain on the tireless and ultimately successful efforts to prevent a mass economic failure. Working with two U.S. presidents and two Treasury secretaries, Dr. Bernanke and his colleagues used every Fed capability, no matter how arcane, to keep the U.S. economy afloat. From his arrival in Washington in 2002 and his experiences before the crisis, to the intense days and weeks of the crisis itself, and through the Great Recession that followed, Dr. Bernanke gives readers a unique perspective on the American economy.
Prologue : I can still stop this... -- Main Street -- In the groves of academe -- Governor -- In the maestro's orchestra -- The subprime spark -- Rookie season -- First tremors, first response -- One step forward -- The end of the beginning -- Bear Stearns : before Asia opens -- Fannie and Freddie : a long, hot summer -- Lehman : the dam breaks -- AIG : "it makes me angry" -- We turn to Congress -- "Fifty percent Hell no" -- A cold wind -- Transition -- From financial crisis to economic crisis -- Quantitative easing : the end of orthodoxy -- Building a new financial system -- QE2 : false dawn -- Headwinds -- Taper capers -- Looking back, looking forward.
Includes bibliographical references and index.
Keywords: Bernanke, Ben; Board of Governors of the Federal Reserve System (U.S.); 2008-2009; Global Financial Crisis, 2008-2009.; Government economists -- United States -- Biography; Banks and banking, Central -- United States; Financial crises -- United States; Monetary policy -- United States; Banks and banking, Central; Financial crises; Government economists; Monetary policy; United States; Biography